Domestic Violence and Its Treatment in the Holy Quran | العنف الأسري وعلاجه في القرآن الكريم - Ahmaddin Ahmad Tohar (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2014)
The conclusion of this paper is that Islam rejects domestic violence as opposed to theprinciples of the Quran and Hadith. More over, the Quran and Hadith command thehusband to treat his wife kindly. The significance of this paper is the formulation of thetreatment proposed by the Quran and Hadits upon domestic violence. This paper usesthematic methodology, by exploring the Quran, Hadith and classical references thatbased on the critical reading.